Intellectual Capital and Challenges of Halal Industry in Malaysia - Muhammad Khalique; Jamal Abdul Nassir Shaari (Indersciences, 2024)
Presently the halal industry has secured overwhelming responses from business professionals as well as from researchers. In 2019, the global halal food market reached a value of US$ 1.8 trillion; it expresses that this industry has strong potential to grow in the near future. The bakery industry is recognised as the main industry of the halal food market. This industry is certifiable under the 'Department of Islamic Development Malaysia (JAKIM)', the sole authority for halal in Malaysia. Despite halal, certification is a strong marketing promotion tool. The main objective of this research was to test the impact of intellectual capital on the business performance of SMEs. Structured survey forms were used to gather the primary data from 185 respondents that were picked through the purposive sampling technique. Results showed that the proposed six hypotheses were supported. This research contributed to the theory of intellectual capital and proposed recommendations for the policy makers and entrepreneurs.